PEDAGOGICAL CONDITIONS FOR TRAINING OF FUTURE EDUCATORS FOR THE FORMATION OF MEDIA CULTURE OF OLDER PRESCHOOLERS - Hrynyk, Yevhen (Theoretical and Methodical Problems of Children and Youth Education, 2022)
In the conditions of progressive informatization of the education system, especially preschool education, the need to train modern educators in the field of media education is growing: for purposeful preparation of the child’s personality for inclusion in the media environment, safe use of it, formation of media culture. The media culture criteria of older pre-schoolers are defined as: media awareness of older preschoolers, which involves awareness of mass communication tools, features of functioning, benefits and harms for a person, genres of media production, and the ability to navigate in the world of information; development of the basics of critical thinking, which will ensure the conscious use of media products based on initial orientation in the media space and understanding of one’s own media needs; knowledge of the rules for using media products that are safe for one’s health, the ability to protect oneself from negative informational influences. Pedagogical conditions for the preparation of future educators for the formation of media culture in older pre-schoolers are considered as: awareness by future educators of the need to form media culture of older pre-schoolers; ensuring interdisciplinary connections in the preparation of future educators for the formation of media culture of older preschoolers; future educators have skills in shaping the media culture of older preschoolers. The specified pedagogical conditions are closely interconnected and complement each other, and only their comprehensive implementation will contribute to the effective solution of the task of training educators to form the media culture of older pre-schoolers. The proposed analysis does not exhaust the relevant issues of the researched problem. The problem of continuity in the formation of media culture of children of older preschoolers and primary schoolchildren remained out of attention; training of teachers for succession in the specified process.